A global review and meta-analysis of applications of the freshwater Fish Invasiveness Screening Kit - Vilizzi, Lorenzo (2019)
The freshwater Fish Invasiveness Screening Kit (FISK) has been applied in 35 risk assessment areas in 45 countries across the six inhabited continents (11 applications using FISK v1; 25 using FISK v2). The present study aimed: to assess the breadth of FISK applications and the confidence (certainty) levels associated with the decision-support tool’s 49 questions and its ability to distinguish between taxa of low-to-medium and high risk of becoming invasive, and thus provide climate-specific, generalised, calibrated thresholds for risk level categorisation; and to identify the most potentially invasive freshwater fish species on a global level. The 1973 risk assessments were carried out by 70 + experts on 372 taxa (47 of the 51 species listed as invasive in the Global Invasive Species Database www.iucngisd.org/gisd/), which in decreasing order of importance belonged to the taxonomic Orders Cypriniformes, Perciformes, Siluriformes, Characiformes, Salmoniformes, Cyprinodontiformes, with the remaining ≈ 8% of taxa distributed across an additional 13 orders. The most widely-screened species (in decreasing importance) were: grass carp Ctenopharyngodon idella, common carp Cyprinus carpio, rainbow trout Oncorhynchus mykiss, silver carp Hypophthalmichthys molitrix and topmouth gudgeon Pseudorasbora parva. Nine ‘globally’ high risk species were identified: common carp, black bullhead Ameiurus melas, round goby Neogobius melanostomus, Chinese (Amur) sleeper Perccottus glenii, brown bullhead Ameiurus nebulosus, eastern mosquitofish Gambusia holbrooki, largemouth (black) bass Micropterus salmoides, pumpkinseed Lepomis gibbosus and pikeperch Sander lucioperca. The relevance of this global review to policy, legislation, and risk assessment and management procedures is discussed.